diff --git a/education/math/MATH1210 (calc 1)/Derivatives.md b/education/math/MATH1210 (calc 1)/Derivatives.md index fcc7342..6b1f876 100644 --- a/education/math/MATH1210 (calc 1)/Derivatives.md +++ b/education/math/MATH1210 (calc 1)/Derivatives.md @@ -122,6 +122,8 @@ $$ \dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2} $ $$ \dfrac{d}{dx} e^x = e^x $$ $$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$ for all $a > 0$ + + # Logarithms For natural logarithms: @@ -129,17 +131,27 @@ $$ \dfrac{d}{dx} \ln |x| = \dfrac{1}{x} $$ For other logarithms: $$ \dfrac{d}{dx} \log_a x = \dfrac{1}{(\ln a) x}$$ -When solving problems that make use of logarithms, consider making use of logarithmic properties to make life easier, eg: +When solving problems that make use of logarithms, consider making use of logarithmic properties to make life easier: $$ \ln(\dfrac{x}{y}) = \ln(x) - \ln(y) $$ +$$ \ln(a^b) = b\ln(a) $$ +## Logarithmic Differentiation +This is used when you want to take the derivative of a function raised to a function ($f(x)^{g(x)})$ + +1. $\dfrac{d}{dx} x^x$ +2. $y = x^x$ +3. $\ln y = \ln x^x$ +4. $\ln(y) = x*\ln(x)$ +5. $\dfrac{d}{dx} \ln y = \dfrac{d}{dx} x \ln x$ +6. $\dfrac{1}{y} \dfrac{dy}{dx} = 1 * \ln x + x * \dfrac{1}{x}$ # Chain Rule $$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$ ## Examples > Given the function $(x^2+3)^4$, find the derivative. Using the chain rule, the above function might be described as $f(g(x))$, where $f(x) = x^4$, and $g(x) = x^2 + 3)$. -5. First find the derivative of the outside function function ($f(x) = x^4$): +7. First find the derivative of the outside function function ($f(x) = x^4$): $$ \dfrac{d}{dx} (x^2 +3)^4 = 4(g(x))^3 ...$$ -6. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$. +8. Multiply that by the derivative of the inside function, $g(x)$, or $x^2 + 3$. $$ \dfrac{d}{dx} (x^2 + 3)^4 = 4(x^2 + 3)^3 * (2x)$$ > Apply the chain rule to $x^4$ @@ -175,7 +187,7 @@ $$ \dfrac{d}{dx} \cot x = -\csc^2 x $$ - Given the equation $y = x^2$, $\dfrac{d}{dx} y = \dfrac{dy}{dx} = 2x$. Given these facts: -7. Let $y$ be some function of $x$ -8. $\dfrac{d}{dx} x = 1$ -9. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\ +9. Let $y$ be some function of $x$ +10. $\dfrac{d}{dx} x = 1$ +11. $\dfrac{d}{dx} y = \dfrac{dy}{dx}$\